Demery Ward: capstone - Ward, Demery, artist (Colorado State University. Libraries, 2015)
The artist's statement: A proverbial "they" let us eat cake; it didn't feed us, so these paintings are made of my slice. Generally, my work incorporates materials which relate to euphemism, allusion, and word play. Cake is a common metaphor for money, especially in excess. In this series, I focus on closed social circles surrounding or within establishments for which a seeming excess of wealth is a prerequisite for participation, construction, or employment. Having a passing-for-middle-class appearance grants me limited access to areas where I am both inside and outside of borders created by class and gender distinction. The scale of these works is meant to reference photography because of its integral role in my process. Combining photography and unconventional materials allows me to embody the journalistic as well as emotive truths of my observations. The surface quality of the cake gives an illusion of traditional, expensive materials while upholding ideas of artificiality and toxicity. Classic compositional devices separate and expel those who do not fit under the frame's hegemony. Reflecting on my experiences at the university and in Fort Collins, I have come to believe that projecting a utopian ideal onto this town is dangerous because it negates realities of hierarchical superiority and aggression. By depicting moments I felt unable to relate to those actively participating in their environments, I address lurking iniquities resulting from utopian negations. Commonalities exist between these environments and their occupants: a uniformity of artificial color and figural postures which suggest exclusivity and alienation.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting